A high-resolution Late Neogene geochemical record of the southeastern margin of the Tibetan Plateau: Constraints on Dali fault system activity and uplift of the Diancang Shan massif. (15th June 2020) - Zhang, Chunxia; Li, Shihu; Zhang, Xiaoyan; Li, Pei; Deng, Chenglong; Guo, Zhengtang
Highlights: We present a high-resolution late Neogene geochemical record from SW China. Increased activation of normal faults in the Dali fault system occurred at 4.2 Ma. The Diancang Shan massif experienced multi-stage uplift during the Pliocene. Abstract: The Dali Basin, located northeast of the Diancang Shan massif, is tectonically controlled by the Dali fault system located along the southeastern margin of the Tibetan Plateau. The sediments in the Dali Basin, thus, record the activity of the Dali fault system and uplift of the Diancang Shan massif during the late Neogene period. In this study, we present the chemical compositions and bulk mineralogical characteristics of fine-grained sediment samples collected from the Dasongping section in the Dali Basin, spanning an interval from 7.6 to 1.8 Ma. Mineral assemblages and geochemical data indicate that the sediment provenance in Dali Basin was a distally-sourced weathered material from 7.6 to 4.2 Ma and changed to a locally-sourced bedrock after 4.2 Ma. This suggests that the Dali Basin was an open lake from 7.6 to 4.2 Ma and changed to a closed lake at 4.2 Ma. The main reason for this change was intensified normal fault activity in the Dali fault system at 4.2 Ma that resulted in the isolation of the Dali Basin and the infilling of local bedrock around the Diancang Shan massif within the Dali basin. Late Pliocene global cooling, marked by the expansion of northern hemisphere glaciation, further intensified the uplift of the Diancang Shan massif at 3.6 Ma, which exposed Paleogene conglomerates east of the Dali Basin. Since 2.7 Ma, the Dali fault system has been dominated by normal extensional processes. The enhanced reactivation resulted in the rapid uplift of the Diancang Shan massif and the rapid infill of the Dali basin by coarse-grained sediments.